2018
DOI: 10.1111/add.14090
|View full text |Cite
|
Sign up to set email alerts
|

Cost‐effectiveness of alternative smoking cessation scenarios in Spain: results from the EQUIPTMOD

Abstract: AimsTo assess the cost‐effectiveness of alternative smoking cessation scenarios from the perspective of the Spanish National Health Service (NHS).DesignWe used the European study on Quantifying Utility of Investment in Protection from Tobacco model (EQUIPTMOD), a Markov‐based state transition economic model, to estimate the return on investment (ROI) of: (a) the current provision of smoking cessation services (brief physician advice and printed self‐helped material + smoking ban and tobacco duty at current lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 37 publications
1
19
0
Order By: Relevance
“…Despite these limitations, results from the present study come along with those reported by others: 0.5 QALYs for former smokers [18], 0.069 QALYs for former smokers [56] and 0.10 QALYs for former smokers [57]. These results are also consistent with previous economic assessments showing that smoking cessation interventions using mobile phones are cost saving [18,58] and cost effective [59]. Interestingly, the program studied herein becomes more cost effective as we increase the age at initiation of the intervention, given that it increases the probability of developing a smoking-related disease and the benefit of smoking cessation is greater, as found by Guerriero et al [18] with larger savings the older the age of the study subgroup.…”
Section: Discussionsupporting
confidence: 92%
“…Despite these limitations, results from the present study come along with those reported by others: 0.5 QALYs for former smokers [18], 0.069 QALYs for former smokers [56] and 0.10 QALYs for former smokers [57]. These results are also consistent with previous economic assessments showing that smoking cessation interventions using mobile phones are cost saving [18,58] and cost effective [59]. Interestingly, the program studied herein becomes more cost effective as we increase the age at initiation of the intervention, given that it increases the probability of developing a smoking-related disease and the benefit of smoking cessation is greater, as found by Guerriero et al [18] with larger savings the older the age of the study subgroup.…”
Section: Discussionsupporting
confidence: 92%
“…The efficacy of free-of-charge smoking cessation interventions has been proven in studies worldwide 11,12 . Additionally, in a recent study, proof of the cost-effectiveness and need for covering the cost smoking cessation interventions under insurance has been reported 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have proven the effectiveness of smoking cessation free-of-charge interventions 10-12 . However, the number of studies that compare the effects of free and paid interventions in real-life settings are limited, both in Turkey and worldwide 9,13 .…”
Section: Introductionmentioning
confidence: 99%
“…There is extensive evidence for the health benefits of smoking cessation. The national and international scientific literature is plagued with economic evaluations of smoking, showing the efficiency of different therapeutic options for smoking cessation, but the economic impact of quitting smoking before surgery has not been evaluated previously. In the present analysis, sources of information have been used to characterize the patient population of the CBA with representative data from across the entire nation, which minimizes the risk of lack of representation.…”
Section: Discussionmentioning
confidence: 99%
“…The combination of pharmacotherapy with medical counselling has been proven to be the most effective and safe option for helping smokers to quit. At present, none of these therapies are funded by the Spanish National Health Systems (NHS) for use in smoking cessation, even though they have been shown to be cost‐effective in Spain. So even at no cost to the NHS, this institution still benefits from their use.…”
Section: Introductionmentioning
confidence: 99%